Negative plate, battery, battery pack and electric equipment
Through the dual-layer negative electrode structure design, the particle size and orientation of the coating are controlled, and the problems of large impedance of the battery and poor lithium ion transmission capacity are solved, and the fast charging performance and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411149640.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-08-08
- Estimated Expiration
- 2044-08-20
AI Technical Summary
The existing batteries have a large impedance during charging and discharging, and have poor lithium ion transmission capabilities, which affects the battery's fast charging performance and cycle life.
Using a double-layer negative electrode sheet structure, the particle size D50 and OI value ratio of the first coating and the second coating are controlled within the range of 0.21≤k1≤0.65 and 18≤k2≤26, respectively. The negative electrode active material particles of the first coating have no obvious orientation, and the negative electrode active material particles of the second coating are oriented significantly in the thickness direction, and the coating is formed through magnetic field induced regulation.
The liquid phase diffusion impedance of the negative electrode sheet is reduced, the fast charging performance and cycle life of the battery are improved, and the dynamic performance of the battery is improved.
Smart Images

Figure CN120453289A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a negative electrode sheet, a battery, a battery pack and electrical equipment. Background Art
[0002] Batteries are common electrochemical devices. During the battery's charge and discharge process, active ions (such as lithium ions in lithium-ion batteries) are intercalated and deintercalated between the positive and negative electrodes. However, due to factors such as the poor transport ability of active ions between the positive and negative electrodes (such as the liquid-phase transport ability of lithium ions in lithium-ion batteries) and the difficulty of embedding active ions in electrode materials, the battery's impedance is high, which is detrimental to the battery's charging performance and also affects the battery's cycle life and other performance characteristics, limiting its application. Therefore, how to reduce impedance while improving battery performance, such as cycle life, is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the Invention
[0003] The present invention provides a negative electrode sheet, a battery, a battery pack and an electrical device, which can reduce the battery impedance and improve the cycle life and other performance of the battery, effectively overcoming the defects of the prior art.
[0004] In one aspect of the present invention, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode coating located on at least one side of the negative electrode current collector, wherein the negative electrode coating comprises a first coating and a second coating located on a side of the first coating away from the negative electrode current collector; the first coating and the second coating each comprise a negative electrode active material; the first coating satisfies 0.21≤k1≤0.65, k1 is the ratio of the particle size D50 of the negative electrode active material in the first coating to the OI value, and the unit of the particle size D50 of the negative electrode active material in the first coating is μm; the second coating satisfies 18≤k2≤26, k2 is the ratio of the particle size D50 of the negative electrode active material in the second coating to the OI value, and the unit of the particle size D50 of the negative electrode active material in the second coating is μm.
[0005] According to one embodiment of the present invention, 0.21≤k1≤0.45.
[0006] According to one embodiment of the present invention, a ratio of the OI value of the negative electrode active material in the first coating layer to the OI value of the negative electrode active material in the second coating layer is 2-52, preferably 30-52.
[0007] According to one embodiment of the present invention, the OI value of the negative electrode active material in the first coating layer is greater than or equal to 21.
[0008] According to one embodiment of the present invention, the OI value of the negative electrode active material in the second coating layer is less than or equal to 12.
[0009] According to one embodiment of the present invention, the particle size D50 of the negative electrode active material in the first coating layer is 6 to 23 μm.
[0010] According to one embodiment of the present invention, the particle size D50 of the negative electrode active material in the second coating layer is 9 to 22 μm.
[0011] According to one embodiment of the present invention, a ratio k3 of the thickness of the first coating layer to the thickness of the second coating layer satisfies 0.14≤k3≤5.47; preferably 0.14≤k3≤2.6.
[0012] According to one embodiment of the present invention, 0.3≤k3≤1.
[0013] According to one embodiment of the present invention, the thickness of the first coating layer is 14 to 96 μm, preferably 25 to 70 μm.
[0014] According to one embodiment of the present invention, the thickness of the second coating layer is 14 to 96 μm, preferably 40 to 85 μm.
[0015] According to one embodiment of the present invention, the negative electrode active material in the first coating layer includes graphite, and the negative electrode active material in the second coating layer includes graphite.
[0016] Another aspect of the present invention provides a battery comprising the above-mentioned negative electrode sheet.
[0017] Another aspect of the present invention provides a battery pack comprising the above-mentioned battery.
[0018] Another aspect of the present invention provides an electrical device comprising the above-mentioned battery or the above-mentioned battery pack.
[0019] The implementation of the present invention has at least the following beneficial effects: by providing a first coating on at least one side of the surface of the negative electrode current collector and a second coating on the side of the first coating away from the negative electrode current collector, and controlling the first coating to satisfy 0.21≤k1≤0.65 and the second coating to satisfy 18≤k2≤26, the two work together to improve the liquid phase mass transfer capacity of the negative electrode sheet, facilitate the transmission of active ions such as lithium ions during the battery charging and discharging process, reduce the liquid phase diffusion impedance of the negative electrode sheet, improve the kinetic performance of the negative electrode sheet, enhance the fast charging performance (charging performance) of the battery, and at the same time, also take into account the improvement of the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the structure of the negative electrode sheet in one embodiment of the present invention.
[0021] Explanation of reference numerals: 1: negative electrode current collector; 2: negative electrode coating; 20: negative electrode active material; 21: first coating; 22: second coating; H1: thickness of the first coating; H2: thickness of the second coating. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific embodiments listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts are within the scope of protection of the present invention.
[0023] In related technologies, batteries generally have problems such as high impedance, poor fast charging performance and cycle performance, which need to be solved urgently.
[0024] For example, at present, the requirements for power batteries to balance energy density, power density and charging speed are becoming increasingly higher. Increasing the surface density of electrode sheets (negative sheets, positive sheets) to construct thick electrodes can achieve higher energy density. However, due to factors such as the intrinsic electrolyte wettability of high-surface-density electrode sheets and the excessively long active ion (such as lithium ion) transmission path, it is not conducive to the active ion kinetic behavior of the battery. During the charging and discharging process of the battery, the active ion transmission resistance is large, which makes the liquid phase diffusion impedance of the battery large, affecting the battery's fast charging performance and cycle life and other performance.
[0025] In view of this, an embodiment of the present invention provides a negative electrode sheet, such as Figure 1 As shown, the negative electrode sheet includes a negative electrode current collector 1 and a negative electrode coating 2 located on at least one side of the negative electrode current collector 1. The negative electrode coating 2 includes a first coating 21 and a second coating 22 located on a side of the first coating 21 away from the negative electrode current collector 1. The first coating 21 and the second coating 22 each include a negative electrode active material 20. The first coating 21 satisfies 0.21≤k1≤0.65, where k1 is the particle size D50 (hereinafter referred to as D1) and the OI value (hereinafter referred to as V OI1 ) ratio, that is, K1=D1 / V OI1 , the unit of D1 is μm; the second coating layer 22 satisfies 18≤k2≤26, k2 is the particle size D50 (hereinafter referred to as D2) of the negative electrode active material 20 in the second coating layer 22 and the OI value (hereinafter referred to as V OI2 ) ratio, that is, K2=D2 / V OI2 , the unit of D2 is μm.
[0026] According to the inventor's research, under the above-mentioned negative electrode sheet structure system, the first coating 21 satisfies 0.21≤k1≤0.65, and the negative electrode active material 20 particles inside it have basically no obvious orientation, and the whole is basically isotropic, thereby improving the interface stability between the negative electrode coating 2 and the negative electrode current collector 1, improving the cycle stability of the negative electrode sheet, and thus improving the cycle life and other performance of the battery; at the same time, the second coating 22 located on the first coating 21 satisfies 18≤k2≤26, and the negative electrode active material 20 particles inside it are obviously oriented in the thickness direction of the negative electrode coating 2, and have a good orientation degree. The oriented negative electrode active material 20 particles can optimize the internal channels of the negative electrode sheet, reduce the tortuosity of the negative electrode sheet, and improve the electrolyte infiltration ability, which is beneficial to the electrolyte infiltration of the negative electrode sheet, and can improve the liquid phase mass transfer ability of the negative electrode sheet, while being beneficial to the active ions in the negative electrode sheet for deintercalation, improving the active ion reaction kinetics, thereby reducing the liquid phase diffusion impedance of the negative electrode sheet, and improving the fast charging performance of the battery.
[0027] Therefore, the embodiment of the present invention can reduce the liquid phase diffusion impedance of the negative electrode sheet and improve the fast charging performance of the battery through the above-mentioned double-layer negative electrode sheet structure design, while taking into account the improvement of battery cycle life and other performance. It can effectively solve the problems of difficulty in balancing the energy density and kinetic performance of the negative electrode sheet and the poor kinetic performance of the high surface density negative electrode sheet.
[0028] Illustratively, k1 may be 0.21, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, 0.43, 0.45, 0.5, 0.55, 0.6, 0.65, or a range consisting of any two thereof.
[0029] In some embodiments, 0.21≤k1≤0.45, which is beneficial for further improving the cycle life and other performance of the battery while maintaining a low liquid phase diffusion impedance of the negative electrode sheet.
[0030] In the embodiment of the present invention, the OI value of the negative electrode active material 20 in the first coating layer 21 is greater than the OI value of the negative electrode active material 20 in the second coating layer 22 (ie, V OI1 >V OI2 ), the ratio of the OI value of the negative electrode active material 20 in the first coating layer 21 to the OI value of the negative electrode active material 20 in the second coating layer 22 (V OI1 / V OI2 )) can be 2 to 52, for example, 2, 5, 10, 20, 25, 30, 35, 40, 45, 50, 52 or a range consisting of any two of them.
[0031] In some embodiments, the ratio of the OI value of the negative electrode active material 20 in the first coating layer 21 to the OI value of the negative electrode active material 20 in the second coating layer 22 (V OI1 / VOI2 )) can be 20 to 52, further can be 30 to 52, and further can be 40 to 52, which is beneficial to improving the interface stability between the negative electrode coating 2 and the negative electrode current collector 1 through the first coating 21 under the above-mentioned negative electrode sheet structure system, and at the same time improving the mass transfer capacity of the negative electrode coating 2 through the second coating 22, thereby reducing the liquid phase mass transfer impedance of the negative electrode sheet. Therefore, based on the synergistic effect of the first coating 21 and the second coating 22, the fast charging performance and cycle life of the battery can be improved.
[0032] Specifically, the OI value of the negative electrode active material 20 in the first coating layer 21 may be greater than or equal to 21 (ie, V OI1 ≥21), V OI1 For example, the range is 21, 22, 25, 28, 30, 32, 35, 35.4, 36, 37 or any two of them, which is beneficial for the negative electrode active material 20 particles in the first coating 21 to have basically no obvious orientation, present better isotropy, further improve the interface stability between the negative electrode coating 2 and the negative electrode current collector 1, and further improve the battery cycle life and other performance while reducing the battery impedance.
[0033] Specifically, the OI value of the negative electrode active material 20 in the second coating layer 22 may be less than or equal to 12 (ie, V OI2 ≤12), for example, less than or equal to 11, less than or equal to 10, or less than or equal to 8, or less than or equal to 5, or less than or equal to 3, or less than or equal to 1, which is beneficial for the negative electrode active material 20 particles in the second coating 22 to have a better orientation in the thickness direction of the negative electrode sheet (also the thickness direction of the negative electrode coating 2), which is beneficial for the active ions in the negative electrode sheet during the charge and discharge process of the battery to be intercalated and deintercalated, improve the reaction kinetics of the active ions, reduce the liquid phase diffusion impedance, and further improve the fast charging performance and cycle performance of the battery.
[0034] In an embodiment of the present invention, the negative electrode active material 20 in the negative electrode coating 2 may include graphite, specifically primary graphite particles and / or secondary graphite particles, that is, the negative electrode active material 20 in the first coating 21 includes graphite, and the negative electrode active material 20 in the second coating 22 includes graphite. Through the double-layer negative electrode sheet structure design, the above-mentioned conditions such as 0.21≤k1≤0.65, 18≤k2≤26 are met, and it can take into account both reducing the impedance of the negative electrode sheet (graphite negative electrode) and improving the cycle life of the negative electrode sheet and other performance.
[0035] Taking the battery charging process as an example, graphite generally has a multi-layered structure. During the battery charging process, active ions (such as lithium ions) begin to intercalate from the end faces of the graphite and enter between the graphite layers, achieving lithium insertion in the negative electrode sheet. In related technologies, to increase the energy density of the negative electrode sheet, thick electrodes with high surface density are usually used, supplemented by a high compaction process. This makes the liquid phase transmission of active ions in the negative electrode sheet and the insertion of active ions into the graphite difficult, and is also not conducive to the electrolyte infiltration of the negative electrode sheet. In turn, the liquid phase impedance of the negative electrode sheet is high, which is not conducive to the battery's charging and cycling performance.
[0036] In the embodiment of the present invention, under the above-mentioned negative electrode sheet structure system, the first coating 21 satisfies 0.21≤k1≤0.65, and the graphite particles inside it have basically no obvious orientation, and are isotropic as a whole, thereby improving the interface stability between the negative electrode coating 2 and the negative electrode current collector 1, improving the cycle stability of the negative electrode sheet, and thus improving the cycle life and other performance of the battery. At the same time, the second coating 22 located on the first coating 21 satisfies 18≤k2≤26, and the graphite particles inside it are obviously oriented in the thickness direction of the negative electrode sheet, and the end faces of the oriented graphite particles are arranged in the thickness direction of the negative electrode sheet, which is beneficial to the intercalation and deintercalation of active ions, improves the active ion reaction kinetics, and is beneficial to the electrolyte infiltration of the negative electrode sheet, and improves the liquid phase mass transfer capacity of the negative electrode sheet, thereby reducing the battery impedance and improving the fast charging performance of the battery.
[0037] In some embodiments, the particle size D50 of the negative electrode active material 20 in the first coating layer 21 may be 6 to 23 μm, for example, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 23 μm, or any two thereof.
[0038] In some embodiments, the particle size D50 of the negative electrode active material 20 in the second coating layer 22 may be 9 to 22 μm, for example, 9 μm, 11 μm, 12 μm, 13 μm, 15 μm, 17 μm, 18 μm, 19 μm, 22 μm, or any two thereof.
[0039] In addition, the ratio k3 of the thickness H1 of the first coating 21 to the thickness H2 of the second coating 22 can satisfy 0.14≤k3≤5.47. By further coordinating the thickness H1 of the first coating 21 and the thickness H2 of the second coating 22, the ratio K3 (k3=H1 / H2) between the two is made within the above range, which is beneficial to further take into account the performance of reducing the liquid phase diffusion resistance of the negative electrode sheet and improving the cycle life of the negative electrode sheet.
[0040] Illustratively, K3 can be 0.14, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.5, 2, 2.3, 2.6, 2.7, 3, 4, 5, 5.47, or a range consisting of any two thereof.
[0041] In some embodiments, 0.14≤k3≤2.6, and can further be 0.3≤k3≤1, which is beneficial for further taking into account the performance of reducing the liquid phase diffusion impedance of the negative electrode sheet and improving the cycle life of the negative electrode sheet.
[0042] In some embodiments, the thickness H1 of the first coating 21 can be 14 to 96 μm, for example, 14 μm, 20 μm, 25 μm, 27 μm, 30 μm, 35 μm, 40 μm, 43 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 96 μm or a range consisting of any two of them, preferably 25-70 μm.
[0043] In some embodiments, the thickness H2 of the second coating 22 is 14 to 96 μm, for example, 14 μm, 20 μm, 25 μm, 27 μm, 30 μm, 35 μm, 40 μm, 43 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 96 μm or a range consisting of any two thereof, preferably 40 to 85 μm.
[0044] The embodiment of the present invention may use a conventional negative electrode current collector 1 in the art. For example, the negative electrode current collector 1 includes copper foil.
[0045] In the embodiment of the present invention, a negative electrode coating 2 (a layer of negative electrode active material 20) can be provided on one surface of the negative electrode current collector 1, or negative electrode coatings 2 (such as 20 layers) can be provided on both surfaces of the opposite sides in the thickness direction of the negative electrode current collector 1. Figure 1 As shown), when negative electrode coatings 2 are respectively provided on the surfaces of the opposite sides of the negative electrode current collector 1, the negative electrode coating 2 on one surface may be the negative electrode coating 2 having the first coating 21 and the second coating 22 as described above, or the negative electrode coatings 2 on the opposite sides of the negative electrode current collector 1 may be the negative electrode coating 2 having the first coating 21 and the second coating 22 as described above.
[0046] In general, the first coating layer 21 further includes a conductive agent and a binder. Based on the total mass of the first coating layer 21, the mass fraction of the negative electrode active material 20 (i.e., the ratio of the mass of the negative electrode active material 20 to the total mass of the first coating layer 21) can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99% or a range consisting of any two thereof, and the mass fraction of the conductive agent can be 0.5% to 15%, for example Such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or any two thereof, the mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or any two thereof.
[0047] In addition, the second coating layer 22 further includes a conductive agent and a binder. Based on the total mass of the second coating layer 22, the mass fraction of the negative electrode active material 20 (i.e., the ratio of the mass of the negative electrode active material 20 to the total mass of the second coating layer 22) can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99% or a range consisting of any two thereof. The mass fraction of the conductive agent can be 0.5% to 15%, for example 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range consisting of any two thereof, and the mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range consisting of any two thereof.
[0048] In an embodiment of the present invention, the conductive agent may be a conventional conductive material in the art, for example, the conductive agent includes one or more of carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fiber.
[0049] In an embodiment of the present invention, the above-mentioned binder can be a conventional bonding material in the field. For example, the binder can include one or more of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0050] In the embodiment of the present invention, k1 (or k2) can be regulated by adjusting parameters such as the particle size and / or OI value of the negative electrode active material 20 in the first coating layer 21 (or the second coating layer 22) to meet the above preset value. The OI value of the negative electrode active material 20 in the first coating layer 21 (or the second coating layer 22) can be regulated by magnetic field induction or other methods. For example, in the process of preparing a negative electrode sheet by a coating method, after the first negative electrode slurry for forming the first coating layer 21 is applied to the surface of the negative electrode current collector 1, a magnetic field is applied to the formed first wet film, and then the film is dried (baked) (specifically, it can be dried under the above-mentioned magnetic field conditions) to form the first coating layer 21. The magnetic field intensity, magnetic field induction time and other conditions can be regulated so that the negative electrode active material 20 particles in the first wet film reach a preset OI value; then, the second negative electrode slurry for forming the second coating layer 22 is applied to the first coating layer 21, and a magnetic field is applied to the formed second wet film, and then the film is dried (baked) or other processes (specifically, it can be dried under the above-mentioned magnetic field conditions) to form the second coating layer 22 on the first coating layer 21 to produce a negative electrode sheet; the magnetic field intensity, magnetic field induction time and other conditions can be regulated so that the negative electrode active material 20 particles in the second wet film reach a preset OI value.
[0051] Generally, after the second wet film is dried, it is uniformly subjected to roller pressing, and then slitting and other processes to obtain a negative electrode sheet.
[0052] In the embodiment of the present invention, conventional magnetic field application methods can be used to apply a magnetic field and regulate magnetic field intensity, magnetic field induction time and other conditions to respectively enable the negative electrode active material 20 in the first coating 21 and the second coating 22 to reach a preset OI value.
[0053] For example, in a specific implementation, after a wet film (a first wet film, a second wet film) is coated on the surface of the negative electrode current collector, the negative electrode current collector coated with the wet film is sequentially passed through a magnetic field region having a magnetic field and an oven having a magnetic field. In this process, the negative electrode active material 20 in the wet film is subjected to a magnetic field. At the same time, while the negative electrode current collector coated with the wet film passes through the oven having a magnetic field, the wet film is dried to form a corresponding coating (a first coating, a second coating), and the negative electrode active material 20 in the coating reaches a preset OI value. Specifically, a magnet with a maximum magnetic field strength of 900mT can be used to provide a magnetic field (that is, the maximum magnetic field strength on the surface of the magnet is 900mT, and TUNKIA can be used). The magnetic field strength of the magnet surface is tested using a TD8620 Gauss meter). The OI value of the negative electrode active material 20 in the formed coating is regulated by adjusting the magnetic field state, the speed of the negative electrode current collector coated with a wet film in the process of passing through the magnetic field area and the oven (conveying speed), and the drying conditions. The conveying speed can specifically be 0.5 to 4 m / s. These regulating means are conventional operations in this field and are not particularly limited thereto.
[0054] In the embodiment of the present invention, the coating, drying, rolling and other processes involved are conventional operations for preparing negative electrode sheets by coating method, and are not particularly limited thereto.
[0055] In an embodiment of the present invention, the first negative electrode slurry and the second negative electrode slurry can be prepared by conventional methods in the art. For example, taking the preparation process of the first negative electrode slurry as an example, the negative electrode active material 20, the conductive agent, the binder, and other components used to form the first coating 21 can be dispersed in a first solvent. The first solvent includes, for example, deionized water and / or N-methylpyrrolidone (NMP) to prepare the first negative electrode slurry, which is then applied to the surface of the negative electrode current collector 1. After magnetic field induction, drying, and other processes, the first coating 21 is formed.
[0056] An embodiment of the present invention further provides a battery, comprising the above-mentioned negative electrode sheet. The battery has advantages corresponding to the above-mentioned negative electrode sheet, which will not be described in detail.
[0057] The battery of the embodiment of the present invention may be a lithium-ion battery (such as a lithium-ion power battery), a solar cell, or other new energy storage batteries.
[0058] Generally, a battery consists of an electrolyte, a cell, and a casing that encapsulates the cell. The electrolyte is injected into the cell within the casing, and the cell includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive and negative electrodes. The cell can be a laminated cell, meaning that the cell is composed of a stacked positive electrode sheet, a separator, and a negative electrode sheet.
[0059] Specifically, the positive electrode sheet includes a positive electrode collector and a positive electrode coating located on at least one side surface of the positive electrode collector. Specifically, the positive electrode coating can be provided on one side surface of the negative electrode collector 1, or the positive electrode coating can be provided on both sides of the positive electrode collector in the thickness direction.
[0060] Specifically, the positive electrode coating (positive electrode active material layer) may include a positive electrode active material, a conductive agent and a binder, all of which may be conventional materials in the art. For example, the positive electrode active material may include a lithium-containing positive electrode active material for a lithium-ion battery, such as one or more of lithium iron phosphate (LFP), lithium cobalt oxide, and a positive electrode ternary material. The positive electrode ternary material may include, for example, a nickel-cobalt-manganese ternary material and / or a nickel-cobalt-aluminum ternary material; the conductive agent may include one or more of carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fiber; the binder may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, an ethylene oxide-containing polymer, polyvinyl pyrrolidone, and polyurethane.
[0061] The embodiment of the present invention may adopt a conventional positive electrode current collector in the art, for example, the positive electrode current collector includes aluminum foil.
[0062] In an embodiment of the present invention, the positive electrode sheet can be prepared by conventional methods in the art, for example, by a coating method. Specifically, the components used to form the positive electrode coating, such as the positive electrode active material, the conductive agent, and the binder, can be dispersed in a second solvent, and the second solvent includes, for example, N-methylpyrrolidone (NMP), to prepare a positive electrode slurry, which is then coated on the surface of the positive electrode current collector. After drying, rolling and other processes, the positive electrode sheet is obtained.
[0063] The electrolyte of the embodiment of the present invention can be a conventional electrolyte in the field. For example, the electrolyte is a non-aqueous electrolyte, which can specifically include an organic solvent and an electrolyte salt. The organic solvent includes, for example, one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and vinylene carbonate (VC). The electrolyte salt may include a lithium salt, and the lithium salt includes, for example, lithium hexafluorophosphate (LiPF6), etc., but is not limited thereto.
[0064] In the embodiment of the present invention, the separator is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from short-circuiting. The embodiment of the present invention can adopt conventional separators in the art without special limitation.
[0065] In the embodiment of the present invention, conventional shell materials in the art may be used to encapsulate the battery cell. The shell may include, for example, a soft packaging material such as an aluminum-plastic film, but is not limited thereto.
[0066] In the embodiment of the present invention, components such as positive electrode sheets, separators and negative electrode sheets can be assembled into a battery by conventional methods in the art. For example, the positive electrode sheets, separators and negative electrode sheets can be stacked to produce a stacked battery cell; the battery cell is then placed in a shell (outer packaging), baked, and then injected with electrolyte, and then packaged, impregnated and other processes to produce a battery.
[0067] An embodiment of the present invention further provides a battery pack including the above-mentioned battery. The battery pack has advantages corresponding to those of the above-mentioned negative electrode sheet, which will not be described in detail.
[0068] Generally, a battery pack includes multiple batteries as described above, which are connected as single cells to form a battery pack. These batteries can be electrically connected using conventional methods in the art, such as series connection, parallel connection, or a combination of these connection methods, without particular limitation.
[0069] An embodiment of the present invention further provides an electrical device, comprising the above-mentioned battery or the above-mentioned battery pack. The electrical device has advantages corresponding to the above-mentioned negative electrode sheet, which will not be described in detail.
[0070] The electrical equipment in the embodiments of the present invention can be conventional electrical equipment in this field, such as power equipment (such as electric vehicles, electric cars), electronic equipment (such as mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (such as watches, bracelets, VR glasses, etc.), energy storage power stations, etc., without special restrictions.
[0071] In an embodiment of the present invention, after obtaining the negative electrode sheet, the cross-section of the negative electrode coating 2 (the cross-section is basically parallel to the thickness direction of the negative electrode sheet) can be observed by a scanning electron microscope (SEM), and the first coating 21 and the second coating 22 can be determined based on the particle size of different regions and their orientation in the thickness direction of the negative electrode coating 2. Characteristics such as the thickness H1 of the first coating 21 and the thickness H2 of the second coating 22 can be measured.
[0072] In specific implementation, a sampler can be used to cut the negative electrode sheet sample, and then an ion milling device can be used to grind and polish the cross section of the negative electrode sheet sample (the cross section is basically parallel to the thickness direction of the negative electrode sheet), and then the cross section of the negative electrode coating 2 is observed by SEM to measure the thickness H1 of the first coating 21, the thickness H2 of the second coating 22 and other characteristics.
[0073] In the embodiment of the present invention, X-ray diffraction (XRD) analysis can be performed on each region of the negative electrode coating 2 (such as the first coating 21 and the second coating 22) to measure the OI value (such as V OI1 、V OI2 Specifically, the OI value indicates the degree of orientation of the negative electrode active material 20 particles in the negative electrode coating 2. The smaller the OI value, the more the negative electrode active material 20 particles in the negative electrode coating 2 tend to be arranged vertically (i.e., the negative electrode active material 20 particles are more parallel to the thickness direction of the negative electrode coating 2). In the XRD analysis results, I1 is the peak intensity of the characteristic peak in the crystal structure direction in which active ions (such as lithium ions) are embedded in the negative electrode active material 20 particles (the peak area (integrated area) of the characteristic peak), and I2 is the peak intensity of the characteristic peak in the crystal structure direction perpendicular to I1 and in which the active ions are more difficult to embed (the peak area (integrated area) of the characteristic peak). That is, if the crystal structure direction in which the active ions are more difficult to embed is perpendicular to the crystal structure direction in which the active ions are embedded in the negative electrode active material 20 particles, then the OI value of the negative electrode active material 20 = I2 / I1. Taking graphite as an example, in the XRD analysis results, I1 is the peak area of the (110) peak of graphite, and I2 is the peak area of the (004) peak of graphite. Then the OI value of the graphite in the negative electrode coating 2 = I2 / I1, that is, the OI value of the graphite in the negative electrode coating 2 is the ratio of the (004) peak intensity of graphite to the (110) peak intensity.
[0074] In the embodiment of the present invention, after obtaining the negative electrode sheet, the average particle size D50 of the negative electrode active material 20 in each region (first coating 21 and second coating 22) of the negative electrode coating 2 can be measured using a laser particle size analyzer. Specifically, a Mastersizer 3000 laser particle size analyzer can be used.
[0075] In a specific implementation, the battery can be disassembled to obtain the negative electrode sheet, and the negative electrode sheet is cleaned with an organic solvent to wash away the electrolyte components such as the electrolyte salt on the negative electrode sheet. Then, the negative electrode sheet is subjected to the above-mentioned SEM, XRD and other analyses to measure the thickness H1 of the first coating layer 21, the thickness H2 of the second coating layer 22, the OI value (V OI1 ), OI value of the negative electrode active material 20 in the second coating layer 22 (V OI2 ), the particle size D50 (D1) of the negative electrode active material 20 in the first coating layer 21, the particle size D50 (D2) of the negative electrode active material 20 in the second coating layer 22, and other characteristics.
[0076] In the embodiment of the present invention, tortuosity is a parameter that describes the pore structure of the negative electrode sheet. The greater the tortuosity, the greater the tortuosity of the negative electrode coating 2, that is, the more tortuous its internal pores are, and the longer the path that the active ions travel from the surface of the negative electrode coating 2 to the negative electrode current collector 1.
[0077] The present invention is further described below through specific examples.
[0078] Example 1
[0079] (1) Graphite, carbon black, and SBR are mixed in a mass ratio of 100:4.8:1.1, and deionized water is added to prepare a first negative electrode slurry; the first negative electrode slurry is applied to both the front and back surfaces of a copper foil, a magnetic field is applied to the formed first wet film, and then dried under the same magnetic field conditions so that the graphite in the formed first coating layer 21 reaches a preset OI value, thereby obtaining a copper foil having the first coating layer 21 formed on the surface (hereinafter referred to as a negative electrode sheet precursor);
[0080] (2) Graphite, carbon black, and SBR are mixed in a mass ratio of 100:4.1:0.9, and deionized water is added to prepare a second negative electrode slurry; the second negative electrode slurry is coated on both the front and back surfaces of the negative electrode sheet precursor, a magnetic field is applied to the formed second wet film, and then dried under the same magnetic field conditions so that the graphite in the formed second coating layer 22 reaches a preset OI value, and then after rolling, slitting, and other processes, a negative electrode sheet is obtained.
[0081] Among them, the structural diagram of the negative electrode sheet is as follows Figure 1As shown, it includes a negative electrode current collector 1 (copper foil), a negative electrode coating 2 located on both the front and back surfaces of the negative electrode current collector 1, and the negative electrode coating 2 on each side includes a first coating 21 and a second coating 22 located on the side of the first coating 21 away from the negative electrode current collector 1.
[0082] Comparative Examples 1 to 4: The only difference from Example 1 is that in the negative electrode sheet, the negative electrode coating 2 is a single layer (i.e., only the first coating 21 or only the second coating 22), and the graphite OI value (V OI1 , or V OI2 ), the ratio of graphite particle size D50 to graphite OI value (K1, or K2) and other conditions are different, see Table 1 for details. Except for the differences shown in Table 1, the other conditions are the same as those in Example 1.
[0083] Examples 5 to 17, Comparative Examples 5 to 9: The difference from Example 1 is that the graphite OI value (V OI1 ), K1 of the first coating 21, graphite OI value of the second coating 22 (V OI2 ), V OI1 and V OI2 The ratio (V OI1 / V OI2 ), K2 of the second coating 22, the thickness H1 of the first coating 21, the thickness H2 of the second coating 22, the ratio K3 of the thickness H1 of the first coating 21 to the thickness H2 of the second coating 22, etc. are different. See Table 1 for details. Except for the differences shown in Table 1, the other conditions are the same as those in Example 1.
[0084] The negative electrode sheets of each embodiment and comparative example were respectively used to conduct the following performance tests. The performance test results are shown in Table 2.
[0085] 1. Liquid phase diffusion impedance test
[0086] Liquid-phase diffusion impedance is measured through electrochemical impedance spectroscopy (EIS). Based on the reference potential, a small-amplitude sinusoidal potential signal of a certain frequency is applied to the electrode. The impedance of the electrode system is measured as it changes with the sinusoidal frequency. The spectrum is then analyzed and fitted to obtain information on the electrode process kinetics and electrode interface structure, further characterizing the impedance value within the battery. The specific test process for liquid-phase diffusion impedance is as follows:
[0087] (1) Assemble two negative electrode sheets and a separator in sequence to form a core (the separator is between the two negative electrode sheets); place the core in an aluminum-plastic film, inject the electrolyte after baking, and obtain a battery to be tested after packaging, impregnation and other processes; wherein the composition of the electrolyte used is as follows: the organic solvent is composed of EC, EMC, DMC, DEC, and VC in a mass ratio of 6:6:2:2:1 (EC:EMC:DMC:DEC:VC=6:6:2:2:1), and the concentration of LiPF6 in the electrolyte is 1 mol / L;
[0088] (2) At room temperature (25°C), a CHI electrochemical workstation was used to perform a liquid phase diffusion impedance test on the battery under test in the frequency range of 300,000 Hz to 0.05 Hz using the IMP-AC Impedance electrochemical test method (the liquid phase diffusion impedance is obtained by processing the real and imaginary parts of the resistance). The liquid phase diffusion impedance test results are shown in Table 2.
[0089] 2. Cycle performance test
[0090] (1) Preparation of positive electrode
[0091] LFP, conductive agent (carbon black and CNTs), and PVDF were mixed in a mass ratio of 100:7.5:2.5, and NMP was added and stirred evenly to prepare a positive electrode slurry;
[0092] The positive electrode slurry is coated on the front and back surfaces of the aluminum foil. After drying and roller pressing, a positive electrode coating is formed on the front and back surfaces of the aluminum foil to produce a positive electrode sheet.
[0093] (2) Battery assembly
[0094] The positive electrode sheets, separators and negative electrode sheets are alternately stacked to assemble into a laminated battery cell; the laminated battery cell is placed in an aluminum-plastic film and assembled into a soft-pack lithium-ion battery through processes such as baking, electrolyte injection, and packaging; the composition of the electrolyte used is as follows: the organic solvent is composed of EC, EMC, DMC, DEC, and VC in a mass ratio of 6:6:2:2:1 (EC:EMC:DMC:DEC:VC=6:6:2:2:1), and the concentration of LiPF6 in the electrolyte is 1 mol / L.
[0095] (3) Battery cycle performance test
[0096] (1) After the battery has rested for 30 minutes, charge it at a constant current of 2C to 3.8V, and then charge it at a constant voltage of 3.8V to 0.05C;
[0097] (2) Let the battery rest for 30 minutes and then discharge it at 0.33C to 2.0V;
[0098] (3) The charge and discharge process of steps (1) and (2) was repeated 500 times. The capacity retention rate was calculated by dividing the 500th discharge capacity by the first discharge capacity. The results are shown in Table 2.
[0099] Table 1 Negative electrode related parameters
[0100] Example <![CDATA[V OI1 ]]> <![CDATA[k1]]> <![CDATA[V OI2 ]]> <![CDATA[k2]]> <![CDATA[V OI1 and V OI2 Ratio of]]> <![CDATA[H1(μm)]]> <![CDATA[H2(μm)]]> <![CDATA[k3]]> Example 1 35.4 0.25 0.7 25.71 50.57 55 55 1.000 Example 2 35.4 0.25 0.7 21.43 50.57 55 55 1.000 Example 3 35.4 0.25 0.7 18.57 50.57 55 55 1.000 Example 4 35.4 0.34 0.7 25.71 50.57 55 55 1.000 Example 5 35.4 0.42 0.7 25.71 50.57 55 55 1.000 Example 6 35.4 0.51 0.7 25.71 50.57 55 55 1.000 Example 7 35.4 0.65 0.7 25.71 50.57 55 55 1.000 Example 8 35.4 0.25 0.7 25.71 50.57 14 96 0.146 Example 9 35.4 0.25 0.7 25.71 50.57 27 83 0.325 Example 10 35.4 0.25 0.7 25.71 50.57 43 67 0.642 Example 11 35.4 0.25 0.7 25.71 50.57 68 42 1.619 Example 12 35.4 0.25 0.7 25.71 50.57 79 31 2.548 Example 13 35.4 0.25 0.7 25.71 50.57 93 17 5.471 Example 14 28.9 0.25 0.7 25.71 41.29 55 55 1.000 Example 15 21.3 0.25 0.7 25.71 30.43 55 55 1.000 Example 16 35.4 0.25 11.6 0.78 3.05 55 55 1.000 Example 17 35.4 0.25 5.7 1.53 6.21 55 55 1.000 Comparative Example 1 35.4 0.25 - - - 110 - - Comparative Example 2 35.4 0.51 - - - 110 - - Comparative Example 3 23.5 0.77 - - - 110 - - Comparative Example 4 - - 0.7 25.71 - - 110 - Comparative Example 5 0.7 25.71 35.4 0.25 0.02 55 55 1.000 Comparative Example 6 35.4 0.17 0.7 25.71 50.57 55 55 1.000 Comparative Example 7 35.4 0.68 0.7 25.71 50.57 55 55 1.000 Comparative Example 8 35.4 0.25 0.7 28.57 50.57 55 55 1.000 Comparative Example 9 35.4 0.25 0.7 14.29 50.57 55 55 1.000
[0101] Table 2 Performance test results
[0102] Example Liquid phase diffusion impedance (Ω) Capacity retention rate (%) Example 1 2.55 90.7 Example 2 2.61 89.7 Example 3 2.68 88.2 Example 4 2.53 88.3 Example 5 2.49 86.8 Example 6 2.47 85.9 Example 7 2.44 85.1 Example 8 2.38 88.2 Example 9 2.42 92.6 Example 10 2.47 93.4 Example 11 2.67 88.9 Example 12 2.82 87.1 Example 13 3.06 86.6 Example 14 2.63 88.9 Example 15 2.71 87.9 Example 16 2.81 86.2 Example 17 2.77 85.7 Comparative Example 1 3.52 81.3 Comparative Example 2 3.46 78.5 Comparative Example 3 3.22 75.9 Comparative Example 4 2.66 79.2 Comparative Example 5 3.41 79.1 Comparative Example 6 2.79 81.8 Comparative Example 7 2.43 82.7 Comparative Example 8 2.74 83.5 Comparative Example 9 2.83 85.3
[0103] From Comparative Examples 1 to 4, it can be seen that when the negative electrode sheet is coated with a single layer, it is difficult to simultaneously reduce the liquid phase diffusion impedance of the negative electrode sheet and improve the battery capacity retention rate. Specifically, in Comparative Examples 1 to 3, the OI value (V OI1 ) is large, the liquid phase diffusion impedance of the negative electrode sheet is large (not less than 3.22Ω), and the capacity retention rate is low (not higher than 81.3%); in Comparative Example 4, the OI value (V OI2 ) is reduced to 0.7. Although it can reduce the liquid phase diffusion impedance of the negative electrode sheet to a certain extent, the cycle life of the battery is seriously deteriorated (the capacity retention rate is less than 80%).
[0104] Compared with Comparative Examples 1 to 4, the negative electrode sheets in Examples 1 to 17 are double-layered, and the first coating layer (lower layer) is controlled to satisfy 0.21≤k1≤0.65, and the second coating layer (upper layer) is controlled to satisfy 18≤k2≤26, which is beneficial to balancing the liquid phase diffusion impedance and cycle life of the negative electrode sheet, and taking into account maintaining a lower liquid phase diffusion impedance of the negative electrode sheet (not higher than 3.16Ω) and a higher cycle life of the battery (capacity retention rate is not less than 85%).
[0105] In addition, it can be seen from Example 1 and Comparative Example 5 that the matching relationship between K1 of the first coating and K2 of the second coating affects the liquid phase diffusion impedance and battery cycle life of the negative electrode sheet. Specifically, although Comparative Example 5 performs double-layer coating and maintains the k value of one layer in the range of 0.21 to 0.65 and the k value of the other layer in the range of 18 to 26, in the negative electrode sheet of Comparative Example 5, the K1 of the lower layer (first coating) is greater than the K2 of the upper layer (second coating) (equivalent to using the second coating in Example 1 as the lower layer ( The first coating layer in Example 1 is used as the upper layer (second coating layer) of Comparative Example 5. The liquid-phase diffusion impedance of the negative electrode sheet is significantly higher than that of the negative electrode sheet in Example 1, and the battery cycle capacity retention rate is significantly lower than that of Example 1. It can be seen that, relative to Comparative Example 5, Example 1 can significantly reduce the liquid-phase diffusion impedance of the negative electrode sheet and improve the battery cycle life by controlling the first coating layer (lower layer) to satisfy 0.21≤k1≤0.65 and the second coating layer (upper layer) to satisfy 18≤k2≤26.
[0106] In addition, it can be seen from Example 1, Examples 4 to 7, Comparative Example 6, and Comparative Example 7 that the K1 of the first coating (lower layer) in the negative electrode sheet is too small (Comparative Example 6) or too large (Comparative Example 7), which will affect the liquid phase diffusion impedance of the negative electrode sheet and the battery cycle life. Specifically, the K1 of the first coating in Comparative Example 6 is less than 0.21, the liquid phase diffusion impedance of the negative electrode sheet is high (2.79Ω), and the battery cycle capacity retention rate is low (81.8%). The K1 of the first coating in Comparative Example 7 is greater than 0.65. Although it can reduce the liquid phase diffusion impedance of the negative electrode sheet to a certain extent, the battery cycle life is still seriously deteriorated (the capacity retention rate is 82.7%). Compared with Comparative Examples 6 and 7, Examples 1 and Examples 4 to 7 can significantly improve the battery cycle life (the capacity retention rate is not less than 85.1%) by controlling the K1 of the first coating within the range of 0.21≤k1≤0.65, while maintaining a low liquid phase diffusion impedance of the negative electrode sheet (not higher than 2.55Ω).
[0107] In addition, compared with Comparative Example 8 (K2>26) and Comparative Example 9 (K2<18), Examples 1 to 3 can reduce the liquid phase diffusion impedance of the negative electrode sheet and improve the cycle capacity retention rate of the battery by controlling the k2 of the second coating (upper layer) within the range of 18≤k2≤26.
[0108] Furthermore, it can be seen from Examples 8 to 13 that, relative to Example 13, Examples 8 to 12 further control the ratio K3 of the thickness H1 of the first coating layer (lower layer) to the thickness H2 of the second coating layer (upper layer) in the negative electrode sheet within the range of 0.14 to 2.6, which is beneficial for further balancing the reduction of the liquid phase diffusion impedance of the negative electrode sheet and the improvement of the cycle life of the battery. In particular, Examples 9 and 10 further control K3 within the range of 0.3 to 1, resulting in lower liquid phase diffusion impedance of the negative electrode sheet and higher cycle capacity retention rate of the battery.
[0109] Furthermore, it can be seen from Examples 1 to 3 and 14 to 17 that, compared with Examples 16 and 17, Examples 1 to 3, 14 and 15 further control the graphite OI value (V OI1 ) and the graphite OI value (V OI2 ) ratio (V OI1 / V OI2 ) is in the range of 30 to 52, which is beneficial to further reduce the liquid phase diffusion impedance of the negative electrode sheet and improve the cycle capacity retention rate of the battery.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode coating located on at least one side of the negative electrode current collector, wherein the negative electrode coating comprises a first coating and a second coating located on a side of the first coating away from the negative electrode current collector; the first coating and the second coating each comprise a negative electrode active material; The first coating layer satisfies 0.21≤k1≤0.65, where k1 is a ratio of the particle size D50 of the negative electrode active material in the first coating layer to the OI value, and the unit of the particle size D50 of the negative electrode active material in the first coating layer is μm; The second coating layer satisfies 18≤k2≤26, k2 is a ratio of a particle size D50 of the negative electrode active material in the second coating layer to an OI value, and the unit of the particle size D50 of the negative electrode active material in the second coating layer is μm.
2. The negative electrode sheet according to claim 1, characterized in that: 0.21≤k1≤0.45。 3. The negative electrode sheet according to claim 1, characterized in that: The ratio of the OI value of the negative electrode active material in the first coating layer to the OI value of the negative electrode active material in the second coating layer is 2-52, preferably 30-52.
4. The negative electrode sheet according to claim 1, characterized in that: The OI value of the negative electrode active material in the first coating layer is greater than or equal to 21.
5. The negative electrode sheet according to claim 1, characterized in that: The OI value of the negative electrode active material in the second coating layer is less than or equal to 12.
6. The negative electrode sheet according to claim 1, characterized in that: The particle size D50 of the negative electrode active material in the first coating layer is 6 to 23 μm.
7. The negative electrode sheet according to claim 1, characterized in that: The particle size D50 of the negative electrode active material in the second coating layer is 9 to 22 μm.
8. The negative electrode sheet according to claim 1, characterized in that: A ratio k3 of the thickness of the first coating layer to the thickness of the second coating layer satisfies 0.14≤k3≤5.47; preferably 0.14≤k3≤2.
6.
9. The negative electrode sheet according to claim 8, characterized in that: 0.3≤k3≤1。 10. The negative electrode sheet according to claim 1 or 8, characterized in that: The thickness of the first coating layer is 14 to 96 μm, preferably 25 to 70 μm.
11. The negative electrode sheet according to claim 1 or 8, characterized in that: The thickness of the second coating layer is 14 to 96 μm, preferably 40 to 85 μm.
12. The negative electrode sheet according to any one of claims 1 to 9, characterized in that: The negative electrode active material in the first coating layer includes graphite, and the negative electrode active material in the second coating layer includes graphite.
13. A battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet according to any one of claims 1 to 12.
14. A battery pack, characterized in that: Including the battery according to claim 13.
15. An electrical device, characterized in that: Comprising the battery according to claim 13 or the battery pack according to claim 14.
Citation Information
Patent Citations
Negative pole piece and secondary battery comprising negative pole piece
CN108807849A
Negative pole piece as well as secondary battery and device comprising negative pole piece
CN113036298A
Negative pole piece and preparation method thereof, secondary battery, battery module, battery pack and device
CN115917780A
Positive plate, preparation method thereof and lithium ion battery
CN117293271A
Secondary battery and electric device
CN118099507A
Cited By
Negative electrode sheet, battery, battery pack and electrical device
WO2026041037A1